Mini-review: possible intermediate hosts of SARS-CoV-2 in post-pandemic times (Revista Sistemas de Producción Agroecológicos, 2023)
SARS-CoV-2, responsible for the disease COVID-19, emerged in December 2019 in Wuhan, China, and quickly became a global pandemic. Efforts have focused on understanding the transmission mechanisms, natural reservoirs, symptoms, and prevention measures for this disease. Several studies demonstrate the susceptibility of animal species to become infected with SARS-CoV-2 after living with a person positive for COVID-19 (anthropozoonosis); the domestic species with the highest susceptibility are cats, since they develop and eliminate the virus very quickly, however, in recent years several studies have established that severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infects to a wide range of animals, including farmed mink, ruminants, ferrets, and other companion animals such as dogs, documented zoo animals that are also susceptible to infection are tigers, lions, pumas, snow leopards, gorillas , otters, and hippopotamus. Due to natural mutation mechanisms of the virus, in mid-2020 different variants emerged, among them the Omicron, which is one of the variants that has generated concern due to the high contagion capacity in animals and the ability to evade the immunological protection provided by vaccines.
Keywords: Domestic animals; coronavirus disease 2019 (COVID-19); severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); interspecies transmission; antigenic variants